2018
DOI: 10.1007/s10459-018-9827-0
|View full text |Cite
|
Sign up to set email alerts
|

Stressing the journey: using life stories to study medical student wellbeing

Abstract: While previous studies have considered medical student burnout and resilience at discrete points in students' training, few studies examine how stressors and resilience-building factors can emerge before, and during, medical school. Our study focuses on students' life stories to comprehensively identify factors contributing to student wellbeing. We performed a secondary analysis of life-story interviews with graduating fourth year medical students. These interviews were originally conducted in 2012 as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
1
21
1
2
Order By: Relevance
“…Social support could have a protective effect for BS in medical students [16,37]. Although this study found a difference of self-rated social support sought by women, which reported to rely more on family and partners than men, this not associated with BS.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Social support could have a protective effect for BS in medical students [16,37]. Although this study found a difference of self-rated social support sought by women, which reported to rely more on family and partners than men, this not associated with BS.…”
Section: Discussioncontrasting
confidence: 76%
“…There is some evidence about protective factors of BS in medical students, as positive life events (marriage, birth or adoption), social support, extracurricular activities and physical activity [8,[15][16][17]. A cross-sectional Spanish study with health professionals found that individuals with higher and moderate self-esteem are associated with higher social support and empathy and lower frequency of BS [18].…”
Section: Introductionmentioning
confidence: 99%
“…Social support could have a protective effect for BS in medical students (16,37). Although this study found a difference of self-rated social support sought by women, which reported to rely more on family and partners than men, this not associated with BS.…”
Section: Discussionmentioning
confidence: 99%
“…23 Medical students report their experiences of emotional abuse within the medical education systems, 24 and mistreatment such as described in our study is associated with student burnout. [24][25][26] In training the next generation of physicians, preceptors may also need to acknowledge and provide additional mentorship around the complexity of their role, and especially their accountability to diverse stakeholders. Within this complex role and environment of multiple accountabilities, preceptors should also teach and role model professionalism through self-improvement.…”
Section: Discussionmentioning
confidence: 99%